Моделирование разрушения сварных швов многослойных комбинированных структур на полимерной основе - Колоскова, Анна Николаевна (НТУ "ХПИ", 2017)
Рассматривается построение моделей разрушения сварных швов многослойных комбинированных структур, изготовленных на полимерной основе. Для оценки прочности соединений построена усовершенствованная модель сварного соединения с использованием стержневой модели полимерной молекулы. По результатам анализа представленных моделей разрушения Т-образного и нахлесточного швов получены в формализованном виде условия прочности с учетом возможных технологических несовершенств при изготовлении соединений. Результаты исследования могут быть использованы для расчетов прочности конструкций на основе многослойных комбинированных структур.

The problems connected to strength analysis of multi-layer combined structures are investigated. The models of destruction of welded joints and strength condition for them are developed. The main result of the investigation is in development of the unified model of destruction of welded joint of polymeric materials. The represented unified model is based on mechanical model of polymer molecule. Using such approach the mechanical models of destruction of T-shaped and lap welded joints are built. It allows to describe the destruction processes and substantiate the significant decrease of their strength in comparison with the basic material. Mechanical models of destruction of T-shaped and lap welded joints of multi-layer combined structures based on polymers are improved by taking into account inter-molecular interaction as a mechanical system. Represented models application allows to estimate the strength conditions for constructions based on multi-layer combined structures in wide variety of manufacturing processes.
Simulation of destruction of weld joints of multi-layer combined structures made on polymeric basis
Keywords: полимер; механическая модель; МКС; сварные соединнения; полимерная пленка; mechanical model